The Effectiveness Of Online Physical Education Learning At Private SMP Abdi Negara Binjai - Hanafi, Ishaq; Lubis, Ade Evriansyah (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
The purpose of this study was to determine the effectiveness of online Physical Education learning at Abdi Negara Binjai Private Junior High School in the 2021/2022 academic year. This research uses quantitative descriptive research design. The data analysis technique in this study uses descriptive statistical analysis which aims to describe the object of research data. The results of research on physical education learning in the network (online) of Abdi Negara Binjai Private Junior High School during the Covid-19 pandemic can be seen from the data that has been obtained, where from a total of 60 students who filled out the questionnaire, there were 31 students with a percentage of 54.1% who stated that it was quite ineffective, 20 students with a percentage of 33.3% who stated ineffective, 7 students with a percentage of 3.5% who stated effective, 3 students with a percentage of 0.6% who stated very ineffective, and 0 students with a percentage of 0.0% who stated very effective. Based on the results of this study, it can be concluded that physical education learning at Abdi Negara Binjai Private Junior High School through online media is quite ineffective.